Long-Term Successive Biochar Amendments Alter the Composition and α-Diversity of Bacterial Community of Paddy Soil in Rice-Wheat Rotation - Xu, Yunxiang; He, Lili; Chen, Jinyuan; Lyu, Haohao; Wang, Yuying; Yang, Lie; Yang, Shengmao; Liu, Yuxue (Frontiers in Environmental Science, 2022)
The specific effect of long-term successive biochar application on soil fertility, α-diversity and composition of bacterial community and their correlations remain unclear. A field experiment was conducted to investigate the effects of straw biochar application on soil physical and chemical properties and the diversity and composition of bacterial community in 12 consecutive crop seasons. Four treatments: BC1 (2.25 Mg•ha−1 biochar), BC5 (11.25 Mg•ha−1 biochar), RS (2.25 Mg•ha−1 rice straw) and a blank control (CK, without biochar or rice straw) were set up. The results indicated that biochar and rice straw reduced the richness indexes of soil bacterial community (Chao1 and ACE by 10.3%–27.4% and 12.2%–26.4%, respectively). High-throughput sequencing results showed that the relative abundance of Cyanobacteria, Bacteroidetes and Actinobacteria increased as the amount of biochar increased, while those of norank_c__Acidobacteria and norank_f__Anaerolineaceae Proteobacteria, Acidobacteria and Nitrospirae decreased. Long-term successive biochar application significantly increased soil pH, available potassium, total organic carbon, total nitrogen, and cation exchange capacity by 5.7%–25.9%, 40.0%–680.0%, 48.0%–217.1%, 51.0%–109.5%, and 5.4%–24.0%, respectively. Soil dissolved organic carbon was slightly decreased by 1.4%–4.0%. Soil pH and C/N were the two major environment factors affecting the composition of the soil bacterial community according to redundancy analysis. Furthermore, the phylogenetic investigation of communities by reconstruction of unobserved states showed that biochar significantly increased the relative abundance information of the functions of the metabolism of other amino acids, metabolism of terpenoids and polyketides, and biosynthesis of other secondary metabolites (p < 0.05). Therefore, long-term successive biochar amendment in rice-wheat rotation systems improved soil fertility, altered the structure of the soil bacterial community and increased the functions of soil bacteria, but decreased the α-diversity of bacterial community. This study will provide technical and theoretical support for rice-straw carbonization and long-term soil remediation from the perspective of microorganisms.